Neutrophil isolation from feline blood using discontinuous Percoll dilutions - Sursal, Neslihan; Cakmak, Ayse; Yildiz, Kader (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
Objective: Some studies have performed in vitro neutrophil isolation from feline blood. The major limiting factor for these studies is the small volume of blood that can be collected without development of potentially life-threatening complications. In the present study we attempted neutrophil isolation from feline venous blood samples using discontinuous Percoll gradients. Material and methods: Blood was collected from the cephalic vein of clinically healthy adult cats. The blood samples were layered on Percoll dilutions (72 %, 63 %, 54 % and 45 %). After centrifugation, the feline polymorphonuclear leukocytes (PMN) accumulated as a band between 72–63 % Percoll dilutions. The total cell count was calculated using light microscopy counts. The percentage of the neutrophils was determined microscopically after staining with Diff-Quik stain. Neutrophil viability was evaluated with a 0.01 % Trypan blue assay. The activation was determined based on intact cell morphology in the isolated neutrophils. Results: The mean PMN number was 22 x 105 per ml (minimum – maximum: 20–26 x 105/ml). Neutrophil homogeneity was > 95 % in the cell suspensions. The viability of isolated neutrophils was > 98 %. The technique did not result in neutrophil activation. Conclusion and clinical relevance: Discontinuous Percoll gradients (72 %, 63 %, 54 % and 45 %) can be used to isolate neutrophils from blood samples of cats. The technique was simple to perform and neutrophil activation was minimal.
Keywords: Cat; PMN; venous blood; isolation; discontinuous Percoll gradients